STUDENTS ERRORS IN USING INTERROGATIVE SENTENCES MADE BY STUDENTS OF SMP NASIONAL BANAU KOTA TERNATE - La Usaha, Hasna Alfiyyah; Ajam, Ali; Latif, Taib (Universitas Khairun, 2023)
This research aims to find out: (1) what are the most dominant types of errors made by class VIII of SMP National Banau Kota Ternate in making interrogative sentences? and (2) what are the factors causing errors made by students of class VIII of SMP National Banau Kota Ternate in using interrogative sentences? This research used descriptive qualitative method; this research involved 20 participants. The research instrument used a test, the test was used to obtain data on the types of errors in interrogative sentences. In data collection, tests were used to obtain data on the types of errors in interrogative sentences. In analyzing the data, there are five steps: Identifying students, Classifying types of errors by using the surface taxonomy strategy proposed by Ellis, Counting the number of errors, Discussing data, and Making conclusions. The results showed that there were 4 types of errors, namely omission, addition, misformation, and misordering. The percentages of the errors are 27 omissions (9.71%), 125 additions (43.10%), 129 misformations (44.48%), and 9 misorderings (3.10%). The most dominant error is misformation (44.48%). And the factor that causes students to often make error in making interrogative sentences is intralingual transfer. Based on the analysis of the students' answer sheets, the misformation type errors made by students are because students are still confused in determining the right auxiliary words. The researcher suggested that teachers give students some exercises to minimize the dominant errors and try to find solutions. For the students, students should learn more by practicing writing regularly.